Integrating Fusarium oxysporum f. sp. strigae into cereal cropping systems in Africa - Venne, J.; Beed, Fenton D.; Avocanh, A.; Watson, A. (Wiley, 2009)
BACKGROUND:Striga hermonthica(Del.) Benth. (witchweed) poses the greatest biological constraint to food production insub-Saharan Africa (SSA). Control options forStrigaare currently largely ineffective or unavailable to farmers, and othermanagement possibilities are urgently needed. Biological control obviates some of the problems of several of the othertechniques and provides a management option that is durable and environmentally responsive. The efficacy ofS. hermonthicacontrol using different formulations of three isolates ofFusarium oxysporumSchlecht. emend. Synder & Hans f. sp.strigaewastested onStriga-resistantandStriga-susceptible varieties of sorghum and maizeunder African field conditions for the firsttime.RESULTS:IsolatesPSM197andFoxy2wereeffectiveinwitchweedrepression,especiallywhenappliedaspestagranules.IsolateM12-4A was less effective under the field conditions investigated. Application of the fungi was generally more beneficial inmaize than in sorghum for the varieties tested. Application of the biocontrol agent caused significant decreases in the numberof floweringStrigaplants, and hence deposition of seeds with impact of enhancing future crop yield.CONCLUSIONS: Synergistic effects between theStriga-resistant maize line andFusarium oxysporumf. spstrigaeled to over90% reduction inStrigaemergence. These results will further encourage the distribution of the isolates tested or selection ofcountry-specific relatives as viable and environmentally safe biocontrol agents to be used againstStriga. Pesta was the mosteffective formulation, while seed coating may be more cost effective.